Flammability and Sensitivity of Materials in Oxygen-Enriched Atmospheres: Ninth Volume 2000
DOI: 10.1520/stp12488s
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Oxygen Compatibility Testing: Effect of Oxygen Aging on Ignition and Combustion Properties

Abstract: The oxygen (O2) compatibility of six polymers used in O2 service was evaluated after 48 h exposures at 121 °C (250 °F) to O2 pressures of 620 and 6200 kPa (90 and 900 psia). Three elastomers were tested: chloroprene rubber (C873-70), fluorocarbon rubber (Viton® A), and silicone rubber (MVQ type); and three thermoplastics were tested: polyhexamethylene adipamide (Zytel® 42), polytetrafluoroethylene (PTFE Teflon® 500A), and polychlorotrifluoroethylene (Neoflon® CTFE M400H). Post-aged changes in mass, dimensions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Also, there appeared to be several dark inclusions (located at six and seven o'clock in Figure 4, left, for example) in the extruded rod stock from Molder 2; however, no attempt was made to characterize the inclusions. Inspection of water (quick)-quenched and air (slow)-quenched compression-molded Neoflon M400H sheet has shown that translucent PCTFEs tend to be more amorphous, while more opaque PCTFEs tend to be more crystalline [9]. Crystallite (spherulite) size differences could also account for the observed variation in translucency.…”
Section: Pctfe Grade Differencesmentioning
confidence: 99%
“…Also, there appeared to be several dark inclusions (located at six and seven o'clock in Figure 4, left, for example) in the extruded rod stock from Molder 2; however, no attempt was made to characterize the inclusions. Inspection of water (quick)-quenched and air (slow)-quenched compression-molded Neoflon M400H sheet has shown that translucent PCTFEs tend to be more amorphous, while more opaque PCTFEs tend to be more crystalline [9]. Crystallite (spherulite) size differences could also account for the observed variation in translucency.…”
Section: Pctfe Grade Differencesmentioning
confidence: 99%